A method for processing cord for reinforcing layer of semi-steel radial tire and tire for new energy vehicle

By preparing composite cords and adopting optimized processing technology, the existing tire cords have been solved, and the existing tire cords have poor heat resistance and insufficient high-speed durability in high-speed environments are achieved, which has achieved significant improvement in tire performance and meets the high-speed driving needs of new energy vehicles.

CN118958019BActive Publication Date: 2025-02-28SHANDONG HUASHENG RUBBER +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411130023.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-02-28
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

The existing tire cords have poor heat resistance and adhesion under high temperature conditions and insufficient high-speed durability in high-speed environments, making it difficult to meet the needs of new energy vehicles for short-term high-speed driving.

Method used

Composite cords are prepared using polyethylene naphthalate fiber and nylon 6.6 fiber, and the performance parameters of the cord are improved by optimizing the processing process, including multiple twisting, immersion in different adhesives and thermal bonding treatments.

Benefits of technology

It significantly improves the heat resistance and high-speed durability of the tires, can meet the high-speed driving needs of new energy vehicles, and improves the overall performance of the tires.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005253695280000071
    Figure GDA0005253695280000071
  • Figure GDA0005253695280000101
    Figure GDA0005253695280000101
Patent Text Reader

Abstract

The present application relates to a method for processing cords for reinforcing layers of semi-steel radial tires and tires for new energy vehicles, belonging to the technical field of vehicle tires. The method comprises the following steps: S1, twisting PEN yarn and PA6.6 yarn twice in the opposite direction of their pre-twisted direction to form a composite cord, and the composite cord has a twist coefficient within the range of 100-150 and a shrinkage rate within 0-0.5% at 100°C and a shrinkage rate within 0-1.5% at 180°C, and the linear density of the composite cord is 2000-3000 dtex; S2, first immersing the composite cord in a first adhesive, drying at 100-120°C for 1-2 minutes, then immersing it in a second adhesive, and drying at 130-150°C for 1-5 minutes; S3, placing the dried composite cord in the range of 190-210°C for thermal bonding, the thermal bonding process takes 80-120 seconds, and in the thermal bonding process, the elongation of the composite cord is 0.5-1.5%. The cord layer prepared by the cord treated in the present application can be used as a tire reinforcement layer to significantly improve the heat resistance and adhesion of the tire and the high-speed durability in a high-speed environment or a high-load environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a method for processing cords for a reinforcing layer of a semi-steel radial tire and a tire for a new energy vehicle, and belongs to the technical field of vehicle tires. Background Art

[0002] Tires are composites of fiber, steel and rubber. Steel and fiber cords reinforce the rubber to form a basic frame structure in the tire. As a reinforcing material for tires, cords need to have properties such as fatigue resistance, shear strength, durability, rebound force, and adhesion to rubber. Various cords made of suitable materials are often used according to the required properties of the tire. For example, in recent years, artificial fibers, nylon, polyester, steel, aromatic polyamide, etc. are often used as materials for preparing cords.

[0003] In the prior art, both PET fiber and nylon fiber are used as cords in the cap layer of tires. However, the adhesion of PET fiber to rubber is poor, and an additional adhesive is required. In addition, the performance of the adhesive in the prior art is relatively poor, resulting in that the durability of the tire at high temperatures still has room for improvement. Although nylon fiber has good adhesion and fatigue resistance to rubber, its low elastic modulus under high temperature conditions leads to poor operational stability, and its high thermal shrinkage force leads to poor tire dimensional stability. In order to improve the above-mentioned problems of PET fiber and nylon fiber, there is a method in the prior art of twisting aromatic polyamide fiber and nylon fiber to obtain a composite cord. However, this method has the problem of relatively high loss, and the heat generation increases due to increased loss, so the life of the tire is relatively short. There is also a method of twisting PET and nylon to obtain multifilament yarn, and then preparing a reinforcing cord for the cap layer. Although it can improve the high-speed durability of the tire to a certain extent, its heat-resistant adhesion at high temperatures still needs to be improved, and its high-speed durability in high-speed environments or high-load environments still needs to be improved. Summary of the invention

[0004] In order to solve the above problems, a method for processing cords for the reinforcement layer of a semi-steel radial tire and a tire for new energy vehicles are provided. The cord processing method provided in the present application and the cord layer prepared by the treated cords, when used as the reinforcement layer of a semi-steel radial tire, can significantly improve the tire's heat resistance and adhesion as well as its high-speed durability in high-speed or high-load environments, thereby meeting the current use requirements of new energy vehicles that often require high-speed driving in a short period of time.

[0005] According to one aspect of the present application, a method for processing a cord for a reinforcing layer of a semi-steel radial tire is provided, the method comprising the following steps:

[0006] S1. PEN yarn is obtained by twisting polyethylene naphthalate fiber, PA6.6 yarn is obtained by twisting nylon 6.6 fiber, and PEN yarn and PA6.6 yarn are twisted twice in the direction opposite to the pre-twisted direction to form a composite cord, wherein the composite cord has a twist factor within the range of 100 to 150, a shrinkage rate within the range of 0 to 0.5% at 100° C., and a shrinkage rate within the range of 0 to 1.5% at 180° C., and a linear density of the composite cord is 2000 to 3000 dtex;

[0007] S2, first immersing the composite cord in a first adhesive, drying at 100-120° C. for 1-2 min, then immersing the composite cord in a second adhesive, and drying at 130-150° C. for 1-5 min;

[0008] S3, placing the dried composite cord in the range of 190-210° C. for thermal bonding, the thermal bonding process takes 80-120 seconds, and during the thermal bonding process, the elongation of the composite cord is 0.5-1.5%;

[0009] The first binder includes silicate, nickel stearate, polybutadiene and hexamethylenetetramine, and the second binder includes resorcinol, formaldehyde and rubber latex.

[0010] Optionally, the first adhesive comprises: 5 to 10 parts of silicate, 3 to 7 parts of nickel stearate, 50 to 100 parts of polybutadiene and 10 to 20 parts of hexamethylenetetramine.

[0011] Optionally, the first adhesive comprises: 5 to 10 parts of silicate, 3 to 7 parts of nickel stearate, 60 to 80 parts of polybutadiene and 15 to 20 parts of hexamethylenetetramine.

[0012] Optionally, the silicate is sodium silicate.

[0013] Optionally, the molecular weight of the polybutadiene is 4000-6000.

[0014] Optionally, the rubber latex is selected from one or more of natural rubber latex, styrene-butadiene copolymer latex, and styrene-butadiene-vinylpyridine copolymer latex.

[0015] According to another aspect of the present application, a cap ply is provided, wherein the cap ply is made of a cord ply treated by any of the above methods.

[0016] According to another aspect of the present application, a semi-steel radial tire for new energy vehicles is provided, wherein the tire includes the cap layer as described above.

[0017] The beneficial effects of this application include but are not limited to:

[0018] The cord processing method for the reinforcing layer of a semi-steel radial tire provided in the present application significantly improves the high-speed durability and heat-resistant adhesion of the tire, and can meet the requirements of short-term high-speed driving scenarios of new energy vehicles.

[0019] The cord processing method for the reinforcing layer of a semi-steel radial tire provided in the present application solves the problem of poor high-speed durability of the cord commonly used in the prior art by optimizing the processing technology of the composite cord prepared by twisting PEN yarn and nylon 6.6 fiber.

[0020] The cord processing method for the reinforcing layer of a semi-steel radial tire provided in the present application further improves the process of dipping the composite cord into an adhesive, and solves the problem of poor heat-resistant adhesion of the tire by combining an immersion process and a thermal bonding process with a first adhesive and a second adhesive.

[0021] The cord processing method for the reinforcing layer of a semi-steel radial tire provided in the present application, during the process of optimizing and screening the components of the first adhesive, found that the tire prepared with sodium silicate had better low rolling resistance and better low loss performance than other silicates. DETAILED DESCRIPTION

[0022] The present application is described in detail below in conjunction with examples, but the present application is not limited to these examples. Unless otherwise specified, the raw materials and catalysts in the examples of the present application are purchased through commercial channels.

[0023] In view of the problems of poor heat resistance and high-speed durability when using PET and nylon fibers to prepare cords for preparing the cord layer of the tire reinforcement layer in the existing technology, in the present application, the inventors prepare composite cords by using PEN and nylon fibers, and optimize the performance parameters of the prepared composite cords. Through subsequent drying conditions and thermal bonding steps, the high-speed durability of the tire can be significantly improved. However, the heat resistance and adhesion are still poor. For this reason, the inventors explored immersing the composite cords in the first adhesive and the second adhesive respectively and then drying them, which significantly improved the heat resistance and adhesion of the tire and can meet the needs of new energy vehicles for short-term high-speed driving scenarios.

[0024] According to one aspect of the present application, a method for processing a cord for a reinforcing layer of a semi-steel radial tire is provided, the method comprising the following steps:

[0025] S1. PEN yarn is obtained by twisting polyethylene naphthalate fiber, PA6.6 yarn is obtained by twisting nylon 6.6 fiber, and PEN yarn and PA6.6 yarn are twisted twice in the direction opposite to the pre-twisted direction to form a composite cord, wherein the composite cord has a twist factor within the range of 100 to 150, a shrinkage rate within the range of 0 to 0.5% at 100° C., and a shrinkage rate within the range of 0 to 1.5% at 180° C., and a linear density of the composite cord is 2000 to 3000 dtex;

[0026] S2, first immersing the composite cord in a first adhesive, drying at 100-120° C. for 1-2 min, then immersing the composite cord in a second adhesive, and drying at 130-150° C. for 1-5 min;

[0027] S3, placing the dried composite cord in the range of 190-210° C. for thermal bonding, the thermal bonding process takes 80-120 seconds, and during the thermal bonding process, the elongation of the composite cord is 0.5-1.5%;

[0028] The first binder includes silicate, nickel stearate, polybutadiene and hexamethylenetetramine, and the second binder includes resorcinol, formaldehyde and rubber latex.

[0029] In one embodiment, the first adhesive comprises: 5 to 10 parts of silicate, 3 to 7 parts of nickel stearate, 50 to 100 parts of polybutadiene and 10 to 20 parts of hexamethylenetetramine.

[0030] In one embodiment, the first adhesive includes: 5 to 10 parts of silicate, 3 to 7 parts of nickel stearate, 60 to 80 parts of polybutadiene and 15 to 20 parts of hexamethylenetetramine.

[0031] In one embodiment, the silicate is sodium silicate.

[0032] In one embodiment, the molecular weight of the polybutadiene is 4,000 to 6,000.

[0033] The composition of the second adhesive is not limited and can be appropriately selected according to the knowledge of the technicians in the field of RFL adhesive and the needs. For example, the common composition includes 0.1-10wt% of resorcinol, 0.1-10wt% of formaldehyde and 1-28wt% of latex, and more preferably, includes 0.5-3wt% of resorcinol, 0.5-3wt% of formaldehyde and 10-25wt% of latex.

[0034] In one embodiment, the rubber latex is selected from one or more of natural rubber latex, styrene-butadiene copolymer latex, and styrene-butadiene-vinylpyridine copolymer latex.

[0035] According to another aspect of the present application, a cap ply is provided. The cap ply is made of a cord ply treated by any of the above methods.

[0036] According to another aspect of the present application, a semi-steel radial tire for new energy vehicles is provided, and the tire includes a cap layer as described above. It should be noted that in the following tests in the present application scheme, semi-steel radial tires containing cord layers are used, and the specific tire preparation steps can refer to the preparation methods commonly used in the art, and in the tests, the semi-steel radial tires are different except for the cord processing methods, and the other preparation conditions and materials used are the same. The cord layer prepared by the cord method in the present application is used in the cap layer, and the semi-steel radial tire uses the cap layer, and the preparation method of the cap layer is also well known to those skilled in the art.

[0037] In the present application, twist factor is defined as the product of the plying level (in turns / meter, according to ASTM D1423) and the square root of the linear density (in decitex) divided by 3000; decitex is one-tenth of Tex, abbreviated as dTex, and Tex refers to the weight (in grams) of one kilometer of filament, strand, yarn or cable; the shrinkage at 120°C and 180°C is tested using the dry heat shrinkage test method commonly used in this application; the elongation is the elongation at a load of 4.5kgf, and the elongation LDR (%) is calculated by the formula (L1-L0) / L0*100, L0 is the initial length of the composite cord, L1 is the length of the composite cord measured after the composite cord is cooled to 24°C under a load of 13% of the cord breaking strength at 120°C for 5 minutes and the load is maintained; in the present application, the reference tires used in the test are all standard semi-steel radial tires prepared by the same method, and relative values ​​are used to measure and characterize the test results.

[0038] The present application also includes some abbreviations, for example, polyethylene naphthalate fiber is abbreviated as PEN, RFL adhesive is the RFL solution commonly used in the art, and nylon 6.6 is abbreviated as PA6.6. Those skilled in the art can distinguish the meaning of the terms in different contexts.

[0039] Example 1

[0040] In this application, the inventors have selected PEN fiber and nylon fiber to prepare composite cord by composite twisting in order to solve the problems of poor high-speed durability and heat-resistant adhesion when PET fiber and nylon fiber are used in tires in the prior art, and have explored and optimized the processing technology of the cord.

[0041] After experiments and optimization, it was finally determined that the processing steps of the cord include: a) twisting polyethylene naphthalate fiber to obtain PEN yarn, twisting nylon 6.6 fiber to obtain PA6.6 yarn, twisting the PEN yarn and the PA6.6 yarn twice in the opposite direction of their pre-twisted direction to form a composite cord, and the composite cord has a twist coefficient in the range of 100 to 150 and a shrinkage rate within 0 to 0.5% and a shrinkage rate within 0 to 1.5% at 100°C and 180°C, and the linear density of the composite cord is 2000 to 3000 dtex; b) first immersing the composite cord in an adhesive, and then drying it at 130 to 150°C for 1 to 5 minutes; c) drying the composite cord The composite cord is placed in the range of 190-210° C. for thermal bonding, the thermal bonding process takes 80-120 seconds, and in the thermal bonding process, the elongation rate of the composite cord is 0.5-1.5%; the adhesive includes resorcinol, formaldehyde and rubber latex, which is a commonly used RFL adhesive in the field, wherein the rubber latex is selected from one or more of natural rubber latex, styrene-butadiene copolymer latex, and styrene-butadiene-vinyl pyridine copolymer latex. In this embodiment, the rubber latex is selected from natural rubber latex. In addition, except for the different preparation conditions in Table 1 below, other preparation conditions and materials used are the same. In the specific optimization process, the different processing conditions are shown in Table 1 below.

[0042] Table 1 Composite cord processing conditions

[0043]

[0044] High-speed durability evaluation is evaluated in the following two ways: 1) Drum durability: The sample tire is mounted on the rim and driven at a specified internal pressure and a specified speed. The speed is increased in stages by 10 km / h every 20 minutes, and then the speed when the failure occurs is measured. The measured speed is shown in the table as a relative value when the value of the reference tire is 100. The larger the value, the higher the durability limit speed and the better the durability. 2) High-speed durability: A drum tire tester is used to continuously drive the tire at a speed of 100 km / h. The tire is continuously driven until the tire is damaged, and the driving distance when the tire is damaged is measured. The result is shown as a relative value when the driving distance of the reference tire is 100. The larger the value, the better the high-speed durability performance. The test results are shown in Table 2 below.

[0045] Table 2 Test results of heat-resistant adhesion and high-speed durability

[0046] serial number Drum durability (relative value) High-speed durability (relative value) Sample 1 127 160 Sample 2 125 156 Sample 3 128 158 Sample 4 118 120 Sample 5 120 124 Sample 6 112 110 Sample 7 110 130 Sample 8 108 120 Sample 9 103 115 Sample 10 121 124

[0047] According to the results in Table 2, samples 1 to 3 have better drum durability and high-speed durability than other samples. It can be seen that the durability of the tire is significantly improved, which has obvious advantages.

[0048] Example 2

[0049] In the present application, the inventors twisted PEN yarn and PA6.6 yarn to form a composite cord, and further optimized the processing technology of the composite cord, especially optimized the parameters of the composite cord before immersion in the adhesive, and significantly improved the drum durability and high-speed durability of the tire through appropriate adhesive drying conditions and thermal bonding process parameters. However, the inventors found that the above improvements could not improve the adhesion between the composite cord and the adhesive, especially the heat-resistant adhesion performance was significantly deteriorated.

[0050] In order to further improve the heat-resistant adhesion, the inventors further conducted experimental research and exploration and determined the following improvement plan: by first immersing the composite cord in a first adhesive including silicate, nickel stearate, polybutadiene and hexamethylenetetramine, and then immersing it in a second adhesive including resorcinol, formaldehyde and rubber latex after drying, and then drying, the tire has good high-speed durability while significantly improving the heat-resistant adhesion.

[0051] The preparation steps of the cord during the experiment include: S1, twisting polyethylene naphthalate fiber to obtain PEN yarn, twisting nylon 6.6 fiber to obtain PA6.6 yarn, and twisting the PEN yarn and the PA6.6 yarn twice in the opposite direction of their pre-twisted direction to form a composite cord, and the composite cord has a twist factor of 120 and a shrinkage rate of 0.2% at 100°C and a shrinkage rate of 1.0% at 180°C, and the linear density of the composite cord is 2400 dtex ; S2, first immerse the composite cord in the first adhesive, dry it at 110℃ for 1min, then immerse it in the second adhesive, and dry it at 140℃ for 3min; S3, place the dried composite cord in the range of 200℃ for thermal bonding, the thermal bonding process takes 100s, and in the thermal bonding process, the elongation of the composite cord is 1.0%; the first adhesive includes silicate, nickel stearate, polybutadiene and hexamethylenetetramine, and the second adhesive includes resorcinol, formaldehyde and rubber latex. The rubber latex is selected from one or more of natural rubber latex, styrene-butadiene copolymer latex, styrene-butadiene-vinyl pyridine copolymer latex, and in this embodiment, the rubber latex is selected from natural rubber latex. The components and content of the first adhesive and the drying conditions after the first adhesive immersion step are shown in Table 3 below. Except for the different conditions in Table 3, the processing method of the cord is exactly the same, the prepared cord layer is used in the same method for preparing the cap layer, and the same method and other materials are used in combination with the cap layer obtained above to prepare a semi-steel radial tire for subsequent performance testing. The test results are shown in Table 4 below.

[0052] Table 3 First adhesive combination and content setting

[0053]

[0054] Among them, sample d does not use the first adhesive, but only immerses the composite cord into the second adhesive, and the cord treatment method is basically the same as the treatment method in Example 1. The high-speed durability test results are detected by the same method as in Example 1, and the heat-resistant adhesive force is evaluated in the following manner: the treated composite cord is buried in an uncrosslinked rubber containing natural rubber as the main component, and pressurized and crosslinked at a temperature of 170°C for 90 minutes. Then, the composite cord is pulled out of the rubber block at a speed of 100 mm / min, and the force required for pulling out is expressed in N / cm, so as to evaluate the heat-resistant adhesiveness. The results are shown in Table 4 below.

[0055] Table 4 Heat-resistant adhesive strength test results

[0056] serial number Heat resistant adhesive strength (N / cm) High speed durability Sample a 225 159 Sample b 223 157 Sample c 220 161 Sample d 184 153 Sample 189 154 Sample f 205 156 Sample g 185 154 Sample h 207 150

[0057] According to the results in Table 4, samples a~h all have good high-speed durability, especially samples a~c have significantly improved heat-resistant adhesion compared to sample d before improvement, and the heat-resistant adhesion is significantly improved. The effect is also better than that of samples e~h, which has obvious advantages.

[0058] Example 3

[0059] Before determining the first adhesive component to be finally used, the inventors conducted experiments on the selection of each component, especially the selection of silicate, which has a great influence on rolling resistance. The silicates used mainly tested were sodium silicate, mica, and asbestos. The inventors found through experiments that when sodium silicate is used as the silicate, the tire prepared therefrom has lower rolling resistance, thereby making the tire less wearable.

[0060] In the rolling resistance test, the rolling resistance of the sample tire when it rolls at a speed of 80 km / h under a specified internal pressure and a specified load is measured by a sliding method. The measured rolling resistance is expressed in Table 5 as a relative value with the value of the reference tire being 100. The larger the relative value, the lower the rolling resistance, that is, the better the rolling resistance.

[0061] Table 5 Low loss test results

[0062] performance Low loss (relative value) Sodium silicate 108 Mica 96 asbestos 102

[0063] According to the results in Table 5, sodium silicate has lower Guidong resistance and thus lower loss compared to other silicates such as mica and asbestos.

[0064] In the present application, in order to solve the problem of poor heat resistance, adhesion and high-speed durability of conventional cords in the prior art when used as cord layers of the reinforcement layer of a semi-steel radial tire, polyethylene naphthalate fiber and nylon 6.6 fiber are used to make a composite cord that meets a specific specification range, and a first adhesive and a second adhesive as well as immersion and drying conditions are used. The cords finally prepared by a suitable thermal bonding process can significantly improve the heat resistance, adhesion and high-speed durability of the tire when used in the reinforcement layer of a semi-steel radial tire. The prepared tire product can meet the current requirements of high-speed driving of new energy vehicles as well as tire durability and heat resistance, and has important market application scenarios and value.

[0065] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for processing cords for a semi-steel radial tire reinforcement layer, characterized in that: The method comprises the following steps: S1. PEN yarn is obtained by twisting polyethylene naphthalate fiber, PA6.6 yarn is obtained by twisting nylon 6.6 fiber, and PEN yarn and PA6.6 yarn are twisted twice in the direction opposite to the pre-twisted direction to form a composite cord, wherein the composite cord has a twist factor within the range of 100 to 150, a shrinkage rate within the range of 0 to 0.5% at 100° C., and a shrinkage rate within the range of 0 to 1.5% at 180° C., and a linear density of the composite cord is 2000 to 3000 dtex; S2, first immersing the composite cord in a first adhesive, drying at 100-120° C. for 1-2 min, then immersing the composite cord in a second adhesive, and drying at 130-150° C. for 1-5 min; S3, placing the dried composite cord in the range of 190-210° C. for thermal bonding, the thermal bonding process takes 80-120 seconds, and during the thermal bonding process, the elongation of the composite cord is 0.5-1.5%; The first adhesive comprises: 5 to 10 parts of silicate, 3 to 7 parts of nickel stearate, 50 to 100 parts of polybutadiene and 10 to 20 parts of hexamethylenetetramine, and the second adhesive comprises resorcinol, formaldehyde and rubber latex.

2. The method according to claim 1, characterized in that The first adhesive comprises: 5 to 10 parts of silicate, 3 to 7 parts of nickel stearate, 60 to 80 parts of polybutadiene and 15 to 20 parts of hexamethylenetetramine.

3. The method according to claim 2, characterized in that The silicate is sodium silicate.

4. The method according to claim 1, characterized in that The molecular weight of the polybutadiene is 4000-6000.

5. The method according to claim 1, characterized in that The rubber latex is selected from one or more of natural rubber latex, styrene-butadiene copolymer latex, and styrene-butadiene-vinylpyridine copolymer latex.

6. A cap layer, characterized in that: The cap layer is made of a cord ply using the cords processed by the method according to any one of claims 1 to 5.

7. A semi-steel radial tire for new energy vehicles, characterized in that: The tire comprises the cap ply as claimed in claim 6.

Citation Information

Patent Citations

  • Polyester fiber cord for reinforcing rubber and method for production thereof

    CN101107395A

  • Tacky finish and textile materials and articles treated therewith

    CN103080224A